Pendampingan Penelitian Tindakan Kelas untuk Guru Sekolah Dasar di Kota Ende - Nining Sar'iyyah; Yuliani Sepe Wangge; Yohana Nono BS; Gregorius Sebo Bito (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
This activity is a community service activity that aims to increase the understanding of elementary school teachers in cluster 3 of South Ende sub-district. This activity was carried out in one of the schools in the cluster, namely SDI Bhoanawa 2 and involved 25 teachers from the three clusters. This mentoring activity is carried out using the lecture, question and answer method and drill which is carried out for one day regarding the preparation of a classroom action research proposal. After the activity was carried out, the teachers' understanding of the PTK proposal had increased between before being given assistance and after being given assistance.